Percepção do ruído hospitalar em funcionários de uma maternidade do município de São Bernardo do Campo - Ferreira, Aidilma Silva (2013)
Noise is an important public health problem. Hospitals, that should provide adequate conditions for acoustic comfort to its patients and employees, are not considered quiet environments, which can bring harm to their health. Objective. To verify the newborn assistance health professionals exposure to occupational noise and to investigate their auditory and non-auditory complaints. Method. The sample consisted of 34 nursing technicians and 32 nursing assistants, all female. The age ranged from 24 to 56 years, with a mean of 37.4. The study of the noise perception was performed using a questionnaire. Sound levels were measured by noise dosimetries on employees during their working hours in day and night shifts. Two Wed007 type 2 dosimeters of the 01dB trademark were used. Statistical analysis was performed using chi-square test to assess the relations between the variables. Results. Most professionals considered the environment to be noisy (98.4%) and believed they, somehow, contributed to ambient noise. The main noise sources reported were equipment and monitoring alarms and people talking. The discomfort, stress, fatigue and irritability were complaints that affected the professionals in a greater degree because of the sense of ambient noise. Statistically significant associations (p <0.05) with stress, fatigue and discomfort in individuals who had the perception that the environment was noisy were found. Professionals who felt more stressed because of the environmental noise perception believed that the noise interfered with their work efficiency (p = 0.002) and thinking (p = 0.010), and reported to be very or extremely annoyed by noise (p = 0.000), bad mood (p = 0.000) and irritability (p = 0.000), being harder to understand others speech (p = 0.000). The most common effects were headache and sensitivity to loud noise. LAeq levels ranged from 70.3 dB (A) to 82.5 dB (A). The minimum levels were in the range of 42.3 dB (A) and 55 dB (A). The maximum levels ranged from 81.3 dB (A) to 94.2 dB (A). Conclusions. Sound levels were higher than those recommended by the acoustic comfort standards. Important statistical associations between the noisy environment and the professionals health complaints were found. The noise can affect oral communication aspects and workers task performance